(untitled) (Journal of Bangladesh Academy of Sciences, 2016)
A method of determining some parameters of water quality, namely calcium and hardness concentrations in the Dupi Tila sand aquifer in Bangladesh using vertical electrical sounding (VES) measurements is presented. The study site comprises an elevated land of the Madhupur Tract representing the Madhupur Clay Formation of the Pleistocene age. Using the relationships between formation water resistivity (Rw) and calcium and hardness concentrations have allowed to relate the latter to formation resistivity (Ro) as functions of porosity (?). The VES derived water quality parameter values seem to differ to some extent from that obtained from laboratory analysis. Provided VES data interpretation is well constrained, it can be a tool that might give some hints of the quality of water. The assumptions to be made to infer water quality from geoelectric sections are presented. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 1, 1-10, 2016